Transformation Lampung Single Guitar in the Digital Era: Perspective Glocalization of Anthony Giddens - Sony Afandi; Yohan Ahmad Zanan; Riyan Hidayatullah (Musikolastika: Jurnal Pertunjukan dan Pendidikan Musik, 2026)
Objective: This study aims to explore how Generation Z musicians preserve and develop the Lampung single-string guitar tradition amid cultural globalization through the use of digital technology and social media. Method: The research employs a netnographic approach, collecting data through in-depth interviews, observations of musicians’ activities on YouTube, TikTok, Instagram, and Facebook, as well as digital content analysis of videos, social media posts, and musical documentation, followed by qualitative analysis to identify transformations and glocalization practices. Results and Discussion: Findings reveal that young musicians actively use digital platforms to promote their works, innovate musical arrangements, and adapt global influences without losing the local cultural identity of the Lampung single-string guitar. Learning and documentation processes through music transcription applications further strengthen efforts to preserve this art, while glocalization practices produce new cultural forms rooted in local tradition. Conclusion: The sustainability of the Lampung single-string guitar relies heavily on the integration of digital technology and active participation of Gen Z musicians, simultaneously reinforcing local cultural existence in a global context and contributing to strategies for preserving traditional arts in the digital era.